Genistein promotes M1 macrophage apoptosis and reduces inflammatory response by disrupting miR-21/TIPE2 pathway - Li Cong; Xiaolin Xie; Sujuan Liu; Liping Xiang; Xiaohua Fu (Elsevier, 2022)
Cardiovascular diseases are a major cause of mortality, and vascular injury, a common pathological basis of cardiovascular disease, is deeply correlated with macrophage apoptosis and inflammatory response. Genistein, a type of phytoestrogen, exerts cardiovascular protective activities, but the underlying mechanism has not been fully elucidated. In this study, RAW264.7 cells were treated with genistein, lipopolysaccharide (LPS), nuclear factor-kappa B (NF-κB) inhibitor, and/or protein kinase B (AKT) agonist to determine the role of genistein in apoptosis and inflammation in LPS-stimulated cells. Simultaneously, high fat diet-fed C57BL/6 mice were administered genistein to evaluate the function of genistein on LPS-induced cardiovascular injury mouse model. Here, we demonstrated that LPS obviously increased apoptosis resistance and inflammatory response of macrophages by promoting miR-21 expression, and miR-21 downregulated tumor necrosis factor-α-induced protein 8-like 2 (TIPE2) expression by targeting the coding region. Genistein reduced miR-21 expression by inhibiting NF-κB, then blocked toll-like receptor 4 (TLR4) pathway and AKT phosphorylation dependent on TIPE2, resulting in inhibition of LPS. Our research suggests that miR-21/TIPE2 pathway is involved in M1 macrophage apoptosis and inflammatory response, and genistein inhibits the progression of LPS-induced cardiovascular injury at the epigenetic level via regulating the promoter region of Vmp1 by NF-κB.